Student Difficulties in Achieving Effective English Learning Skills - Andhina Ika Sunardi; Nafiah, Rofiatun; Nafisatul Lutfi; Agnes Nora Eko Wahyu Utami (Acitya: Journal of Teaching and Education, 2025)
This study aims to describe the learning difficulties of Yogyakarta Administrative Management Academy students in acquiring English language skills. The survey targeted 205 students enrolled in the even semester of the 2023-2024 academic year. Qualitative description was used in data analysis. From the results of this study, two factors of difficulty were found, namely internal and external. The causes of students' learning difficulties from internal factors such as low level of intelligence, low aptitude in English subjects, lack of interest in learning, and low motivation to learn. Students attend only out of obligation and to get good grades and complete assignments, not to learn English as an international language that is so important today. The external factors that affect students who have difficulty learning English include a lack of support for the use of English at home or in the community, as well as limited opportunities to use English outside the classroom. Keywords: learning difficulties, competence, English language